Kenaikan Berat Badan Bayi Usia 1 Bulan Pada Bayi Berat Badan Lahir Rendah - Ati Sulianty; Baiq Yuni Fitri Hamidiyanti; Intan Gumilang Pratiwi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Growth at the age of 1 month is an important beginning for babies with a history of low birth weight (LBW). Gestational age, gender and birth weight are factors that must be considered in the growth process. The purpose of this study was to determine the relationship between gestational age, gender and birth weight with weight at 1 month of age.Observational analytical research with a retrospective cohort design and quantitative study methods was conducted from January to December 2024. The samples used were all LBW infants whose weight was measured at the age of 1 month, as many as 80 infants who met the inclusion criteria. The samples were weighed and the results were recorded on the KMS sheet for LBW infants and the results were plotted on the 1 month old weight growth chart. Furthermore, the results were categorized into two groups: appropriate and inappropriate.The research shows the results for gestational age and baby weight at 1 month with a value (p-value = 0.041). Gender with 1 month baby weight with value (p-value = 0.022) and history of birth weight with 1 month baby weight with value (p-value = 0.037). The conclusion is that there is a relationship between gestational age, gender and birth weight history with the weight of a 1 month old baby